Biocompatibility of RealSeal, its primer and AH Plus implanted in subcutaneous connective tissue of rats (Journal of Applied Oral Science, 2011)
OBJECTIVE: This study tested rat connective tissue response to RealSeal, RealSeal primer or AH Plus after 7, 15, 30, 60 and 90 days of implantation. MATERIAL AND METHODS: Thirty Wistar rats had subcutaneous sockets created on their back and received four implants each of polyethylene tubes containing one of the materials tested according to the groups: AH (AH Plus Sealer); RS (RealSeal Sealer); RP (RealSeal Primer); CG (control group - empty tube). After histological processing, sections were analyzed to identify the presence of neutrophils, lymphocytes and plasma cells, eosinophils, macrophages and giant cells, as well as fibrous capsule and abscesses, by an examiner using light microscope. Kruskal-Wallis and multiple-comparisons test were used for statistical analysis. Significance level was set at 5%. RESULTS: Lymphoplasmacytic infiltrate scores significantly higher than those of the control group were observed at 14 and 60 days in AH group, and at 90 days in RS group (p